Conversational Repair and Human Understanding - Raymond, Geoffrey; Hayashi, Makoto; Sidnell, Jack (Cambridge University Press, 2013)
Humans are imperfect, and problems of speaking, hearing and understanding are pervasive in ordinary interaction. This book examines the way we 'repair' and correct such problems as they arise in conversation and other forms of human interaction. The first book-length study of this topic, it brings together a team of scholars from the fields of anthropology, communication, linguistics and sociology to explore how speakers address problems in their own talk and that of others, and how the practices of repair are interwoven with non-verbal aspects of communication such as gaze and gesture, across a variety of languages. Specific chapters highlight intersections between repair and epistemics, repair and turn construction, and repair and action formation. Aimed at researchers and students in sociolinguistics, speech communication, conversation analysis and the broader human and social sciences to which they contribute - anthropology, linguistics, psychology and sociology - this book provides a state-of-the-art review of conversational repair, while charting new directions for future study.